FAKE PRODUCT IDENTIFICATION USING MACHINE LEARNING (International Journal of Food and Nutritional Sciences, 2022)
The problem of recognizing counterfeit (fake) products is a tedious task in certain cases and can be dangerous when it comes to medical products. It becomes easier to produce and sell fake products if an individual does not check the details of the product properly. This paper suggests a better solution using Artificial Intelligence for non-tech-savvy customers who can scan the product with the help of a mobile application to identify, if the product received is fake or original. The major focus will be on the detection of logos (both image and textual representation).